Effectiveness of the Neonatal Discharge Program for Very Low-Birth-Weight Infants on Parental Efficacy and Psychological Distress. Issue 4 (October 2018) - Shandra Bos, Lakshmi; Shorey, Shefaly; Kulantaipian, Tamill Salvee; Sng, Jane S. P.; Tam, Wilson W. S.; Koh, Serena S. L.
Abstract : This pilot study aimed to (i) evaluate the effectiveness of a neonatal discharge program, (ii) identify relationships between parent and infant factors and parental efficacy and psychological distress, and (iii) identify ways to improve the neonatal discharge program. A quasiexperimental 1-group pretest/posttest design was used. Through consecutive sampling, 42 participants were recruited. Data were collected using self-report questionnaires. Self-administering instruments gathered data on parental efficacy and psychological distress as well as feedback and recommendations on the intervention. A significant increase in parental efficacy and a reduction in psychological distress were observed from pre- to postdischarge intervention. Significant relationships were found between parental efficacy and infants' gestational age, birth weight, gender, and participants' level of education, and a significant relationship was found between psychological distress and number of children from previous pregnancies. Moreover, an Internet-based program, in addition to the face-to-face teaching, was identified as a preferred option to aid in information retention. It is important to evaluate and enhance the neonatal discharge program to suit the parents of today while providing them with informational and emotional support. Future studies should explore parental coping and the long-term effects of their infant's birth and the intervention.